Pelaksanaan Pendidikan Agama Pada SMA Swasta - Wahab Wahab (Analisa: Journal of Social Science and Religion, 2010)
This research is a comparative study which compared to the impact  PAIprivate high school implementation islamic faundation that uses foundationand Diknas curriculum. The purpose of this study are 1) to know the differencebetween the religious behavior of students who obtain teaching religion  fromdiknas curiculum  and PAI  foundation curicula, 2) to identify differences inreligious behavior among students of class X, XI, and XII at the PAI religious  prifate high school  foundation. The results showed (1) students who get educationfrom foundation curicula is better than the setudent who  get education  PAI from diknas curicula .  2). The student of class  XII student behavior is betterthan the behavior in grade XI.